Innovative strategies for accelerated human resource development in South Asia student assessment and examination special focus on Bangladesh, Nepal, and Sri Lanka. (Innovative strategies for accelerated human resource development series., 2017)
Assessment of student learning outcomes (ASLO) is one of the key activities in teaching and learning. It serves as the source of information in determining the quality of education at the classroom and national levels. Results from any assessment have an influence on decision making, on policy development related to improving individual student achievement, and to ensure the equity and quality of an education system. ASLO provides teachers and school heads with information for making decisions regarding a students progress. The information allows teachers and school heads to understand a students performance better.